Exploring determinants of M-government services for the Ministry of Housing: a study from the citizens perspective in Oman - Shamsul Arrieya bin Ariffin, Aslina binti Saad, Salem Abdullah Salem Garfan (Tanjung Malim, 2024)
Exploring determinants of M-government services for the Ministry of Housing: a study from the citizens perspective in Oman by Shamsul Arrieya bin Ariffin, Aslina binti Saad, Salem Abdullah Salem Garfan